Muhammadiyah’s Concept Of Ijtihad On Hadith: A Case Study Of Friday Prayers For Women In The Tarjih Decision - Bilqis Qurroti A'yun; Ida Rochmawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This research is based on several problems, including women often being the subject of debate in aspects of worship. Although the Qur'an places men and women in equal positions and opportunities, several hadiths in their words seem to give women a lower position than men. One of the focuses of this research is related to differences in views regarding the law of attending Friday prayers for women, especially in the context of Muhammadiyah fatwas. This problem is related to the basic principles in Islamic jurisprudence regarding the legal status of worship and the existence of evidence that is used as a basis for determining its permissibility or obligation. This research is a qualitative research using a library research approach whose primary data refers to the Muhammadiyah Tarjih Decision Collection as the main reference in understanding Muhammadiyah ijtihad, the hadith narrated by Sunan Abu Dawud Index Number 106 as the main object of study in determining the law of Friday prayers for women, and books of hadith (Kutubut Tis'ah). The final results obtained from this research are, first, the hadith narrated by Abu Dawud, index number 1067. If it is linked to the Muhammadiyah rules in the process of interpreting and understanding hadiths, then the above hadith is classified as rule 6, namely the mursal sahabi hadith can be used as hujjah if there is a qarinah that shows a connection. Second, the results of the interview and the findings of the principles of Muhammadiyah's openness, they view that the issue of Friday prayers for women is not obligatory as stated in the hadith in the book of Sunan Abu Dawud, index number 1067 in the Muhammadiyah fatwa that the hadith is a form of rukhsah given by Allah SWT. Third, in general, all major Islamic mass organizations in Indonesia agree that Friday prayers are not obligatory for women.